2023
DOI: 10.1002/jaba.1037
|View full text |Cite
|
Sign up to set email alerts
|

The multiple‐stimulus‐without‐replacement preference assessment tool and its predictive validity

Hugo Curiel,
Emily S. L. Curiel,
Santos Villanueva
et al.

Abstract: This study demonstrates the use of two web‐based programs, one to identify video preferences and the other to assess their reinforcing effects. We used the Multiple‐Stimulus‐Without‐Replacement Preference Assessment Tool (MSWO PAT) to identify the video preference hierarchies of seven participants, ages 4–11 years old. We then used a customized reinforcer assessment program that arranged a concurrent‐chains preparation with programmed conjugate schedules of reinforcement. Button presses emitted by participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…The results from the current study also provide further proof-of-concept support for the use of conjugate assessments. Curiel et al (2024) used a conjugate preparation, similar to the one described by MacAleese et al (2015), to validate brief and full MSWO assessments with school children with speech impairments and intellectual disabilities. After Curiel et al identified a hierarchy of preferred video categories for each participant via the MSWO, their participants completed the conjugate assessment wherein they pressed a button at a rate of twice per second to either maintain or increase the audio and visual clarity of videos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from the current study also provide further proof-of-concept support for the use of conjugate assessments. Curiel et al (2024) used a conjugate preparation, similar to the one described by MacAleese et al (2015), to validate brief and full MSWO assessments with school children with speech impairments and intellectual disabilities. After Curiel et al identified a hierarchy of preferred video categories for each participant via the MSWO, their participants completed the conjugate assessment wherein they pressed a button at a rate of twice per second to either maintain or increase the audio and visual clarity of videos.…”
Section: Discussionmentioning
confidence: 99%
“…Several applied and translational studies have shown the potential of synchronous and conjugate schedules for evaluating stimulus preference and the efficacy of those stimuli to serve as reinforcers (Cook et al, 2024;Curiel et al, 2024;Davis et al, 2021;Diaz de Villegas et al, 2020;Falligant et al, 2018Falligant et al, , 2020MacAleese et al, 2015;Peterson et al, 2024; see also Pel aez-Nogueras et al, 1996). Davis et al (2021) used a conjugate preparation to measure 54 college students' preferences for pictorial stimuli.…”
mentioning
confidence: 99%
“…The arrangement of conjugate schedules may have a variety of applications to affect behavior. One avenue to explore in applied and translational research is using conjugate schedules for simplifying preference assessments (Curiel et al, 2023;Rapp, 2008;Saunders & Saunders, 2011).…”
mentioning
confidence: 99%
“…Recently, researchers have developed dynamic conjugate preparations for translational (e.g., Davis et al, 2021;Falligant et al, 2018Falligant et al, , 2020MacAleese et al, 2015;Peterson et al, 2024) and applied (Curiel et al, 2023;Deochand et al, 2020;Diaz de Villegas et al, 2020;McHugh et al, 2022) studies. Briefly summarized, results from MacAleese et al (2015), Curiel et al, 2023;Falligant et al (2018Falligant et al ( , 2020, and Deochand et al (2020) illustrate how (a) behavior under conjugate schedules changes reliably to various auditory and visual stimulus events and (b) extinction of conjugately reinforced behavior gives rise to dynamic changes in response rate and response force. These characteristics illustrate the immediate direct effects and the acute sensitivity that conjugate schedules have on responding.…”
mentioning
confidence: 99%
“…Rapp argued that the ideal simulation for automatically reinforced behavior is a translational preparation with a conjugate schedule of reinforcement. Researchers have since taken advantage of the observation by using conjugate schedules to evaluate translational questions pertaining to stimulus preference (Curiel et al, 2024;Davis et al, 2021;MacAleese et al, 2015) and response force during extinction (e.g., Falligant et al, 2018Falligant et al, , 2020.…”
mentioning
confidence: 99%